Interprofessional Education in Action: Piloting an Online Interprofessional Learning Event for Counseling and Occupational Therapy Students - Megan A Whitbeck; Carrie Griffiths (Teaching and Supervision in Counseling, 2025)
Interprofessional education (IPE) is a training modality that aims to help two or more disciplines learn about, from, and with each other, that enhances outcomes for clients (WHO, 2010). Two faculty members, one from counseling and one from occupational therapy, collaborated to design and implement a virtual pilot IPE event focused on enhancing student role delineation in interdisciplinary treatment teams, communication, and professional behaviors. Using guided questions provided prior to the event, students shared information about their disciplines, roles in client treatment teams, professional responsibilities, and potential collaboration opportunities between occupational therapists and counselors. This manuscript provides an overview of developing and facilitating a virtual IPE event in counseling and implications for implementing IPE in counselor education curricula.
Keywords: Interprofessional education; counseling; occupational therapy; virtual interprofessional education; interdisciplinary collaboration